2012
DOI: 10.17221/38/2012-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Development of spruce (Picea abies [L.] Karst.) target (crop) trees in pole-stage stand with different initial spacing and tending regime

Abstract: This paper presents findings of a twenty-year investigation of silviculture-production in a 40-year-old afforested spruce pole-stage stand located in a mountain region. The stand was established by four different spacing models: (i) 1.5 × 1.0 m, (ii) 2.5 × 1.0 m, (iii) 2.5 × 1.5 m, and (iv) 2.5 × 2.5 m. Three alternatives were studied for each of these spacing models. These were: (i) geometrical (line) thinning, (ii) selective thinning and (iii) no tending. During the period of our research the above-mentioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Previous stand level studies have shown that a thinning-free regime with short rotation periods could increase the profitability compared to conventional management of Norway spruce stands (Subramanian et al 2016a). However, it is difficult to conclude that such an approach would improve profitability at a landscape level because of the risks associated with a thinning-free management, such as increased risk of natural mortality and snow damage (Rössler 2006;Štefančík 2012). The SR strategy also presents few selection opportunities and thus little scope to tune future wood quality, and prevents forest owners from deriving income via thinning at an early stage.…”
Section: Trade-offs and Synergies In Alternative Management Regimesmentioning
confidence: 99%
“…Previous stand level studies have shown that a thinning-free regime with short rotation periods could increase the profitability compared to conventional management of Norway spruce stands (Subramanian et al 2016a). However, it is difficult to conclude that such an approach would improve profitability at a landscape level because of the risks associated with a thinning-free management, such as increased risk of natural mortality and snow damage (Rössler 2006;Štefančík 2012). The SR strategy also presents few selection opportunities and thus little scope to tune future wood quality, and prevents forest owners from deriving income via thinning at an early stage.…”
Section: Trade-offs and Synergies In Alternative Management Regimesmentioning
confidence: 99%
“…However, the drawbacks of a forest management regime without thinning must also be considered, such as the risk for increased natural mortality, risk of snow damage [66,67] and the lack of both selection opportunities and early incomes from thinnings. Furthermore, in such a regime, the cost of planning would be less due to wider initial spacing (Table 1), however there might be negative effects on future wood quality due to the lack of selection [68].…”
Section: Discussionmentioning
confidence: 99%
“…Међутим, овакав начин газдовања са смрчевим културама је повезан са већим трошковима сече и израде тањег проредног материјала, који има малу економску вредност. Новији резултати вишедецениј-ских истраживања на трајним огледним површинама у састојинама смрче, у којима су вршене високе и селективне прореде у раном периоду, показали су да се таквим приступом интензивира првенствено раст стабала у дебљину после прореде, а примарно стабала будућности, која су била предмет неге, што је доприносило бржем повећању њихових димензија и тиме скраћивању производног циклуса, али и смањењу степена виткости, односно повећању стабилности стабала након прореде (Slodičák, Novák, 2003;Nilsson et al, 2010;Štefančík, 2012). Такође, резултати дугорочних истраживања ефеката прореда у културама смрче генерално указују да састојине имају позитивну реакцију на прореде, независно од старосне доби у периоду када се врше комерцијалне прореде (Mäkinen, Isomäki, 2004a;2004b).…”
unclassified